2022
DOI: 10.3390/ani12223164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Replacement of Maize Silage and Soyabean Meal with Mulberry Silage in the Diet of Hu Lambs on Growth Performance, Serum Biochemical Indices, Slaughter Performance, and Meat Quality

Abstract: Maize silage has a high demand for fertilizer and water. As an unconventional feed resource, mulberry silage has the potential to replace most maize silage and to alleviate the shortage of roughage in the mutton sheep industry in China. The purpose of this experiment was to study the effect of the replacement of maize silage and soyabean meal with mulberry silage in the diet of Hu lambs on growth performance, serum biochemical indices, slaughter performance, and meat quality. Ninety-six healthy Hu lambs were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…Firmicute s and Proteobacteria were the dominant phyla in both the control and SB-treated groups. This result was consistent with the results of a previous study (Wang et al, 2022 ). However, the relative abundance of Proteobacteria was reduced in other treatment groups.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Firmicute s and Proteobacteria were the dominant phyla in both the control and SB-treated groups. This result was consistent with the results of a previous study (Wang et al, 2022 ). However, the relative abundance of Proteobacteria was reduced in other treatment groups.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, the pH in the PP-, PP_SB-, and LP_PP_SB-treated groups was 4.58, 4.70, and 4.26, respectively. A previous study observed that Pediococcus can grow well under a pH range of 4.3–4.9 during ensiling (Wang et al, 2022 ). Additionally, the inoculation of Pediococcus was 1 × 10 6 log 10 CFU/g FW, 5 × 10 5 log 10 CFU/g FW, and 5 × 10 5 log 10 CFU/g FW in these groups, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation